1995
DOI: 10.2337/diab.44.10.1233
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Hybridization of Interleukin 6 in Diabetic Nephropathy

Abstract: Increased mesangial expansion is one of the most characteristic histological changes in diabetic nephropathy (DN). Although the pathogenesis of DN remains unclear, recent studies associate interleukin (IL) 6 with mesangial proliferative glomerulonephritis. To elucidate the expression and localization of IL-6 mRNA in renal tissues of patients with DN, a high-resolution in situ hybridization using digoxigenin-labeled oligonucleotide was performed. Patients were divided into three groups based on light microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 23 publications
(31 reference statements)
2
94
0
5
Order By: Relevance
“…It is well known that inflammation plays important roles in the pathogenesis of DN32, 33. In contrast, several studies showed that psychosocial factors are closely related with the induction of inflammation and immune system malfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that inflammation plays important roles in the pathogenesis of DN32, 33. In contrast, several studies showed that psychosocial factors are closely related with the induction of inflammation and immune system malfunction.…”
Section: Discussionmentioning
confidence: 99%
“…IL6 is another cytokine probably involved in mediating inflammatory damage to the kidney: IL6 is present in glomerular-resident cells and interstitial cells in the renal tissue of patients with diabetic nephropathy [14] and the cytokine is capable of inducing severe mesangial proliferation and matrix enlargement in proliferative glomerulonephritis [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cortical mRNA expression of IL-6 is increased in diabetic kidney in comparison with normal rodents and is positively associated with elevated urinary concentrations of albumin (Navarro et al, 2006). Similarly, other researcher published work on interstitial expression of IL-6 mRNA in human renal tissue from individuals with diabetes, correlates with histological features of interstitial injury (Suzuki et al, 1995). IL-10, an important Th2 cytokine, exerts predominantly anti-inflammatory and immunosuppressive effects (Zimmet, 1999).…”
Section: Resultsmentioning
confidence: 96%
“…In 1995, Suzuki et al, (1995) reported that serum levels of IL-6 were significantly higher in patients with T2DN than the levels observed in diabetic patients without nephropathy, which suggests that IL-6 may have a role in the pathogenesis of DN. Later, Suzuki et al, (1995) performed situ hybridization of IL-6 in diabetic nephropathy, analyzed kidney biopsies in patients with DN by high-resolution in situ hybridization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation